The Experience of Health Care Workers Infected by Corona Virus Diseases-19 - Siti Rochanah; Irma Nurbaeti (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: The number of health workers on the front lines have been affected by COVID-19 and some of them have been infected by COVID-19 since the outbreak of COVID-19. Understanding healthcare workers experience is important to get their meaning and expression. Purpose: The purpose of this study is to explore the experiences of healthcare workers infected by COVID-19. Methods: Qualitative phenomenological approach is carried out in this study with phenomenological analysis for data interpretation. Data collection was carried out by in-depth interviews with 12 health workers who were infected by COVID-19 both during treatment and after being treated at a non-government hospital in Jakarta, Indonesia. Results: We found five themes followed by fourteen subthemes. The themes were (1) The meaning of COVID-19 for her/himself, (2) The first feelings of being infected by COVID-19, (3) Experience of Clinical symptoms, (4) Experience of psychological and social disorders, (5) Experience in accessing health services. Conclusion: Health workers infected by COVID-19 have had several positive and negative experiences. This research can provide an in-depth understanding of the lives of health workers infected by COVID-19. Proper planning and support is important to reduce health worker problems both physically and psychologically.